Effects of the combination of intermittent fasting and physical exercise on autophagic and leptin pathway in the hypothalamus of obese mice - Oliveira, Luciana da Costa (2022)
Diet-induced obesity is associated with persistent low-grade inflammation in the hypothalamus which promotes the development of central leptin resistance. This inflammatory process involves dysregulation of the hypothalamic autophagic pathway, compromising the dynamics of activation/inhibition of the orexigenic AgRP neurons (associated with the sensation of hunger) and the anorectic POMC (associated with the sensation of satiety), deregulating energy homeostasis and predisposing to weight gain. Studies point out that fasting (IF) and physical exercise (E) are capable of modulating hypothalamic inflammatory proteins and activate/inhibit neuropeptides; in this sense, we hypothesized that there is possible that the combination of the protocols (IF and execise) would bring more expressive effects in the reestablishment of hypothalamic sensitivity to leptin. Objective: to investigate the effect of the association of IF with combined E on inflammatory, autophagy and leptin pathways in the hypothalamus of high-fat diet fed mice. Methodology: mice were divided into 5 groups: two controls: standard diet (C) and high fat diet (HF); and 3 intervention groups: high fat diet-trained (HF-T), high fat diet-intermittent fasting (HF-IF), and high fat diet-intermittent fasting and trained (HF-IFT). The methods used were: immunohistochemistry, Immunoblotting, RT-PCR, ELISA and ITT, in addition to the analysis of body mass and food intake. Mains Results: compared to the HF group, only the groups that performed the IF showed a reduction in the evaluated hypothalamic inflammatory proteins and an increase in POMC mRNA expression. After intraperitoneal stimulation with leptin, the HF-IFT group showed an increase in pSTAT3 in ARQ and VMH compared to the HF, HF-T and HF-IF groups. The three interventions showed lower caloric intake and body mass compared to the HF group, suggesting a correction in hyperphagic behavior and resistance to diet-induced weight gain. Conclusion: these data indicate that the beneficial effects of the combination of IF and physical exercise on energy homeostasis may be associated with improved leptin sensitivity in ARC and VMH, probably due, at least in part, to the reduction of hypothalamic SOCS3 and improved autophagic response.